Innovation and productive development in Paraguay. An analysis of the post-pandemic challenges of Covid19 - Olmedo Barchello, Selva (2024)
Innovation is a strategic objective for achieving inclusive economic growth; therefore, strengthening local research, development, and innovation capacities is necessary and challenging for Paraguay. Thus, the study aims to identify the main post-pandemic challenges for innovation and productive development for Paraguay in 2020-2022. The methodology applied is qualitative-quantitative, through a review of the literature in this field and the use of databases of national and international organizations. The results show a low innovative capacity and, therefore, a low productive development. In conclusion, this leads to the question of the direction that should be taken or the foundations on which to prioritize Paraguay's productive transformation towards a post- pandemic era, in which it is crucial to have local strategic capacities.